(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research seeks to shed light on the number of people who have been compensated in compulsory insurance from civil liability as a result of their exposure to traffic accidents, What is the role of the National Insurance Company in spreading awareness and insurance culture to the public, And the extent to which they are aware of the existence of this type of insurance, especially that they pay the compulsory insurance premium by refueling gasoline, as well as studying and analyzing the number of traffic accidents during a period of time (10 years), and was there compensation equivalent or close to the number of these accidents, and how many premiums were collected from The Iraqi Ministry of Oil on compulsory insurance and what is the percentage of compensation from these premiums. The researcher relied on data collection methods through scientific sources and research, as well as the actual figures from the National Insurance Company, the General Traffic Department and the Ministry of Planning for the period 2011-2020, through which data was analyzed and ratios extracted, in addition to the use of the spss statistical method (Pearson) in analyzing the data of The hypothesis of correlation between variables to measure statistical relationships and the hypothesis of influence to measure the effect of the independent variable on the dependent variable. And through the results of the data analysis, we found that there is no awareness on the part of the victim and his lack of awareness of the existence of this right, in addition to that the number of victims who have been compensated is very small compared to the number of those affected.